Intersection of the Academic Research Consortium – high bleeding risk criteria in patients undergoing PCI for acute coronary syndromes: insights from a high-volume single centre registry. (25th November 2020) - Nicolas, J; Cao, D; Claessen, B; Sartori, S; Roumeliotis, A; Goel, R; Chandiramani, R; Stefanini, G; Turfah, A; Chen, S; Dangas, G; Baber, U; et al.
Abstract: Introduction: Patients presenting for percutaneous coronary intervention (PCI) with acute coronary syndromes (ACS) often have overlapping bleeding and ischaemic risk factors that offset the long-term success of PCI and limit the post stenting therapeutic options. Aiming at improving outcomes following PCI, the Academic Research Consortium (ARC) recently published a set of major and minor criteria that identify, a priori, patients at high bleeding risk (HBR). Indeed, knowledge of these risk factors will help in optimization of pre-procedural therapy and minimization of post intervention complications. Nonetheless, the actual prevalence of these criteria among patients undergoing PCI for ACS is not well known. Purpose: To determine the intersection and distribution of ARC-HBR major and minor criteria in a real-world ACS population presenting for PCI. Methods: In this analysis, we included all patients who presented with ACS to a high-volume PCI centre from 2012 to 2017 and underwent PCI with 2nd generation drug-eluting stent (DES) implantation. Patients were then classified as HBR if they met ≥1 major or ≥2 minor criteria according to the ARC-HBR definition. Baseline clinical and procedural characteristics were extracted from each patient electronic health records. The most common exclusive intersections of ARC-HBR major and minor criteria were quantitatively visualized using an Upset Plot. Results: Only 44.6% (n=2, 717) of ACS patients (n=6, 097) fulfilled the ARC-HBR definition. There were significant differences in baseline clinical characteristics between HBR and non-HBR groups: age (71.4±11.5 vs. 60.9±10.3 years, p<0.001), females (40.7% vs. 25.5%, p<0.001), cerebrovascular disease (19.5% vs. 3.9%, p<0.001), and diabetes (55.4% vs. 42.1%, p<0.001). The prevalence of active smoking, a major risk factor for bleeding, was higher in the non-HBR group (20.6% vs. 9.9%, p<0.001). The most frequent major and minor criteria were severe anemia (n=1, 072) and age ≥75 (n=1, 264), respectively. The top five criteria intersections were: severe anemia (n=215), age ≥75 and moderate chronic kidney disease (CKD) (n=145); moderate CKD and mild anemia (n=142); age ≥75 and mild anemia (n=140); age ≥75, moderate CKD, and mild anemia (n=130) (Figure 1). Conclusion: Among patients who have undergone PCI for ACS, a significant proportion of individuals fulfilled the ARC-HBR definition. Severe anemia was the most prevalent major criteria. Different combinations of minor criteria, mainly age ≥75, moderate CKD and mild anemia, represented the most common intersections. Funding Acknowledgement: Type of funding source: None